BENTUK KOMUNIKASI TEKS PADA KUMPULAN CERPEN CORAT-CORET DI TOILET KARYA EKA KURNIAWAN - Asri Furoidah; Alberta Natasia Adji (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
The Form of Text Communication in Eka Kurniawan’s Corat-coret di Toilet Short Story Collection. The purpose of this study is to find the method of text communication in the Corat-coret di Tolet short stories collection. The form of this study is a literary study with structural analysis methods as offered in the narrative theory of Gerard Gennette. The results of the study are the classification of the text communication method of short stories namely: zero and fixed internal focalization; subsequent and simultaneous narrating times; intradiegetic-heterodiegetic, extradiegetic-heterodiegetic, and intradiegetic-homodiegetic types of narrating level and person; the character and writer as a narrator. The findings of the classification of text communication methods indicate the existence of a gender bias that alienates women's position in the story.